Clinical and surgical outcomes of patients with peritoneal mesothelioma discussed at a monthly national multidisciplinary team video‐conference meeting. Issue 2 (30th January 2020) - Brandl, A.; Westbrook, S.; Nunn, S.; Arbuthnot‐Smith, E.; Mulsow, J.; Youssef, H.; Carr, N.; Tzivanakis, A.; Dayal, S.; Mohamed, F.; Moran, B.J.; Cecil, T.
Abstract : Background: Peritoneal mesothelioma (PM) is a rare primary neoplasm of the peritoneum with an increasing incidence worldwide. Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) has shown promise as a treatment strategy. A national PM multidisciplinary team (national PM MDT) video‐conference meeting was established in the UK and Ireland in March 2016, aiming to plan optimal treatment, record outcomes and provide evidence for the benefits of centralization. This article reports on the activities and outcomes of the first 2·5 years. Methods: Between March 2016 and December 2018, patients with PM, referred to peritoneal malignancy centres in Basingstoke, Birmingham, Manchester and Dublin, were discussed by the national PM MDT via video‐conference. The MDT was composed of surgeons, radiologists, specialist nurses and pathologists. Patients were considered for CRS and HIPEC if considered fit for surgery and if radiological imaging suggested that complete surgical cytoreduction could be achieved. Morbidity and mortality following surgery were analysed. Survival analysis following MDT discussion was conducted. Results: A total of 155 patients (M : F ratio 0·96) with a mean(s.d.) age of 57(17) years were discussed. To date, 22 (14·2 per cent) have had CRS and HIPEC; the median Peritoneal Cancer Index for the surgical group was 17·0. Complete cytoreduction was achieved in 19 patients. Clavien–Dindo grade I–II complications occurred in 16 patients; there was no grade III–IV morbidity or 30‐day in‐hospital mortality. The median follow‐up for the whole cohort was 18·7 months, and the 2‐year survival rate from time of first review at the national PM MDT was 68·3 per cent. Conclusion: The centralized national PM MDT was effective at selecting patients suitable for CRS and HIPEC, reporting a good outcome from patient selection. Abstract : The focus of this study was to demonstrate experience in understanding, managing and treating peritoneal mesothelioma, a rare disease, and explore how this was facilitated through the establishment of a national multidisciplinary team (MDT), a model that may be useful for other rare diseases. This centralized national peritoneal mesothelioma MDT was effective at selecting patients suitable for cytoreductive surgery and hyperthermic intraperitoneal chemotherapy, and advising on the optimal treatment strategy for patients unlikely to benefit from surgery. Peritoneal mesothelioma and national MDT Abstract : Antecedentes: El mesotelioma peritoneal ( peritoneal mesothelioma, PM) es una neoplasia primaria del peritoneo muy poco frecuente, con una incidencia creciente en todo el mundo. La cirugía citorreductora ( cytoreductive surgery, CRS) con quimioterapia intraperitoneal hipertérmica ( hyperthermic intraperitoneal chemotherapy, HIPEC) se ha mostrado prometedora como estrategia de tratamiento. En marzo de 2016, se organizó una reunión por videoconferencia del equipo multidisciplinar nacional de PM ( national PM multi‐Disciplinary Team, MDT) en el Reino Unido e Irlanda, con el objetivo de planificar un tratamiento óptimo, registrar los resultados y proporcionar evidencia de los beneficios de la centralización. Este manuscrito presenta las actividades y los resultados de los primeros 2, 5 años. Métodos: Entre marzo de 2016 y diciembre de 2018, 155 pacientes con PM, remitidos a centros de cirugía oncológica peritoneal en Basingstoke, Good Hope Hospital en Birmingham, Christie Hospital en Manchester y Mater Misericordiae en Dublín, fueron discutidos en el National PM MDT a través de una videoconferencia. El MDT estaba compuesto por cirujanos, radiólogos, enfermeras especializadas y patólogos. Los pacientes fueron considerados para CRS e HIPEC si se determinaba que eran aptos para la cirugía y si las imágenes radiológicas sugerían que se podía lograr una citorreducción quirúrgica completa. Se analizó la morbilidad y mortalidad después de la cirugía. Se realizó un análisis de supervivencia tras la discusión en el MDT. Resultados: En total, se discutieron 155 pacientes (tasa varón/mujer 0, 96) con una edad media de 57 ± 17 años. Hasta el momento, 22 (14, 2%) habían sido sometidos a CRS y HIPEC y la mediana de PCI en el grupo quirúrgico fue de 17, 0. La citorreducción completa se logró en 19 (86, 4%), las complicaciones de Clavien‐Dindo grado I/II ocurrieron en 16/22, sin morbilidad de grado III/IV, ni mortalidad a los 30 días. La mediana de seguimiento fue de 15, 0 meses y la supervivencia a los 2 años desde el momento de la revisión en el National PM MDT fue del 66, 7%. Conclusión: El National PM MDT centralizado fue eficaz en la selección de pacientes adecuados para CRS e HIPEC, presentando un buen resultado a partir de dicha selección.